PROBLEM AUTENTISITAS HADIS DALAM KAJIAN KONTEMPORER: TINJAUAN LITERATUR ATAS KRITIK SANAD-MATAN, PENDEKATAN HISTORIS, DAN AUTENTIKASI DIGITAL - Yoga Mahath Pandika; Nur Efendi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
The study of hadith authenticity is one of the central issues in hadith studies because it is directly related to the validity of traditions attributed to Prophet Muhammad. This study aims to map the problem of hadith authenticity in contemporary academic literature using the Systematic Literature Review method. The data were obtained from scholarly journal articles relevant to hadith authenticity, hadith criticism, hadith historicity, and digital hadith authentication. The data were analyzed using thematic analysis by classifying the literature based on research focus, method, main findings, and contribution to hadith studies. The findings show that the problem of hadith authenticity can be mapped into several layers, namely transmission problems, matn substance problems, historicity problems, scholarly authority problems, and the problem of hadith dissemination in digital spaces. Sanad criticism and matn criticism remain the main foundations of hadith authentication, while common link theory anisnad-cum-matn analysis contribute to a more critical understanding of the historical transmission of hadith. Digital authentication emerges as a response to the spread of hadith in digital media, but it still requires methodological validation from classical hadith sciences. This study emphasizes the need for an integrative model of hadith authenticity that combines transmission validation, textual-substantive validation, historical analysis, and digital technology.